GUNUNG API PURBA CANDISARI : IDENTIFIKASI AWAL, KARAKTERISASI PEMBENTUKAN, POSISI STRATIGRAFI DAN POTENSI PEMANFAATANNYA - Oky Sugarbo (KURVATEK, 2021)
Abstract In the Southern Mountain Zone, many volcanic rocks that products of the Tertiary Volcanic Arc are exposed. In this zone, a lot of research has been carried out, but research about ancient volcanoes and the center of the ancient eruption has not been carried out thoroughly, so it is necessary to carry out further research related to the ancient volcanism of the Southern Mountains. The purpose of this research is to identify the preliminary study about existence of ancient volcanoes based on field and laboratory data with the aim of knowing the character, genesis, stratigraphic position and the potential of ancient volcanoes that produce many volcanic rocks. The research method used is a surface mapping method that supported by laboratory data such as petrographic and rock geochemistry using X-Ray Flourecence. In the study area, there were indications of ancient volcanoes based on image data, lithology, stratigraphy, petrography and geochemistry with facies association in the upper proximal facies. Stratigraphically, the Ancient Volcanic Rocks of Canndisari are under the Semilir Formation but not part of the Kebo-Butak Formation. The abundance of volcanic rocks can be used as class C mining materials. In addition, it is necessary to carry out further studies on the existence of hydrothermal alteration in the research area which may be used by local communities because altered rocks have economic value. Keywords: lava, genesis, volcanism, ancient, Candisari.